Integrating Mobile Learning into Nomadic Education Programme in Nigeria: Issues and perspectives - Aderinoye, Rashid A.; Ojokheta, K. O.; Olojede, A. A. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
The establishment of the Nigerian National Commission for Nomadic Education in 1989 created wider opportunities for an estimated 9.3 million nomads living in Nigeria to acquire literacy skills. This commission was struck to address low literacy rates among pastoral nomads and migrant fishermen, which put literacy rates at 0.28 percent and 20 percent respectively (FME, 2005). To improve the literacy rate among Nigeria’s nomadic populations, the National Commission for Nomadic Education employed various approaches such as onsite schools, ‘shift system’ schools with alternative intake, and Islamiyya (Islamic) schools, to provide literacy education to its nomads. A critical appraisal of these approaches by the commission, however, shows that very few of the schools were actually viable. This paper explores why these approaches have not notably helped to improve the literacy rate among Nigeria’s nomadic people. Thus, there remains a need for alternative approaches to educational delivery. In face of the revolutionary trends taking place in information and communication technologies (ICTs) in Nigeria, there is now opportunity to embrace mobile learning using low cost mobile technologies (i.e., mobile phones) to enhance the literacy rates among Nigeria’s nomadic people, some of whom are enrolled in Nigeria’s current Nomadic Education Programme. Indeed, mobile telephones with simple text messaging features, for example, are prevalent in many parts of Nigeria. This paper explores the needs and advantages of integrating mobile learning into Nomadic Education programmes in Nigeria to ensure a successful implementation and achievement of the goals of the programme.